(untitled) (CIPEEX, 2022)
PARTIAL AGENESIS OF THE CORPUS CALLOSUM (PACC) IS A CONGENITAL MALFORMATION THAT GENERATES A DYSFUNCTION IN THE CONNECTION BETWEEN THE CEREBRAL HEMISPHERES, WHICH CAN IMPAIR LATERALIZED HEMISPHERIC FUNCTIONS, SUCH AS EMOTIONS, LANGUAGE, AND VISUAL SPATIAL PROCESSING. DUE TO COMPENSATION MECHANISMS AND BRAIN PLASTICITY, THERE ARE PATIENTS WITH HETEROGENEOUS CLINICAL MANIFESTATIONS, FROM ASYMPTOMATIC PATIENTS TO THOSE WITH MORE SEVERE CASES. THE OBJECTIVE OF THIS CASE REPORT IS TO DESCRIBE THE CASE OF A 14-YEAR-OLD PATIENT WITH ACC, THAT HAS AN EASE FOR LEARNING LANGUAGES. THE PATIENT’S MOTHER REALIZED HER DAUGHTER’S PATHOLOGY AFTER BIRTH, WHEN SHE SHOWED SIGNS SUCH AS NEURODEVELOPMENTAL DELAY, ASTHENIA AND A COMPREHENSION DIFFICULTY. THE SYMPTOMS BECAME MORE ACUTE WHEN THE PATIENT WAS 6 YEARS OLD, HER NEUROLOGIST REQUESTED IMAGING TESTS, WHICH MADE IT POSSIBLE TO CORRELATE THE IMAGING DIAGNOSIS WITH THE PATIENT’S CLINICAL CONDITION. CURRENTLY, MULTIDISCIPLINARY ACTIVITIES AND DRUG TREATMENT WITH PHENOARBITAL AND CARBAMAZEZINE. THE RESEARCH IN QUESTION SOUGHT TO RATIFY THE IMPORTANCE OF FURTHER EXPLANATIONS ABOUT THE CASE, WITH THE AIM OF PREVENTING RISK FACTORS AND IMPROVING THE QUALITY OF LIFE OF PATIENTS WITH PACC. THEREFORE, THE EARLY OBSERVATION OF THE MANIFESTATIONS AND THE RATIFICATION OF THE PREVIOUS DIAGNOSIS TEND TO PROMOTE GREATER SATISFACTION IN THE TREATMENT.